“PELATIHAN MENGGAMBAR DENGAN MENGEKSPLORASI IMAGINASI DENGAN TEKNIK POP-UP” (RPTRA Dharma Suci- Jakarta) - Streit, Aprilia Kartini; Erlyana, Yana (Universitas Bunda Mulia, 2019)
For an educator, it is directed how to utilize this imagination to improve children's creativity in studying. Imaginative play naturally occurs in children, starting when children begin to think concretely until the child becomes an adult, but the habit of imaginative thinking is not maximized, needs to be taught and strengthened throughout his life. One of children's creativity is by drawing and using their imagination. Children need practice in imagining because they also need practice in applying every basic skill in their lives. This research uses a collaborative and participatory action research method (PAR). In this community service activity, the target participants are children aged 6-8 years in the North Jakarta Dharma Suci RPTRA. The results of the training of these activities children tend to be enthusiastic in following the material given. Children tend to be interested in learning more about making drawing, coloring and pop-ups. And it can be seen that children are able to imagine making simple stories with pictures and pop ups added.